2011
DOI: 10.1515/integ.2011.027
|View full text |Cite
|
Sign up to set email alerts
|

There are No Multiply-Perfect Fibonacci Numbers

Abstract: We show that no Fibonacci number (larger than 1) divides the sum of its divisors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…But we have seen already that q divides V 2 i n for at most one value of i, and so the claim is proved. Now (22) and (23) yield that ω (V 2 i n ) 2 for all but O g (1) indices i with 0 i < s, as desired. 2…”
Section: Lemma 5 (See Ljunggrenmentioning
confidence: 75%
See 3 more Smart Citations
“…But we have seen already that q divides V 2 i n for at most one value of i, and so the claim is proved. Now (22) and (23) yield that ω (V 2 i n ) 2 for all but O g (1) indices i with 0 i < s, as desired. 2…”
Section: Lemma 5 (See Ljunggrenmentioning
confidence: 75%
“…For every two indices i, j ∈ C, the greatest common divisor of U n i /U n i+1 and U n j /U n j+1 is supported on the primes dividing g − 1. So to prove (19), it is enough to show that for all but O g (1) …”
Section: Lemma 5 (See Ljunggrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Work in showing infinite classes of natural numbers which are not perfect or multiperfect has been developed by Luca, who has shown that no Fibonacci number is perfect [6], that no element of a Lucas sequence with odd parameters is multiperfect [7] and, with Broughan, González, Lewis, Huguet and Togbé, that no Fibonacci number is multiperfect [2].…”
Section: Introductionmentioning
confidence: 99%